Pendidikan Sex Dini Terhadap Pemahaman Siswa Tentang Batasan Privasi Tubuh Di SDN 08 Matobe - Marsya Dwi Anjelina; Winasti Audia Ningsih; Ristika Indriani; Ropi’ah Ropi’ah; Eka Nabila Surya Ghina; Zulhendra Zulhendra (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Sex education plays an important role in equipping children and adolescents with knowledge about the body, gender differences, puberty changes, and the prevention of sexual violence. The low implementation of sex education in Indonesia, including in the Mentawai Islands, contributes to high rates of risky sexual behavior, unwanted pregnancies, and cases of sexual violence that are often resolved through customary mechanisms. This educational activity aims to enhance students' knowledge at SDN 08 Matobe regarding the concept of sex education, forms of sexual harassment, and self-protection strategies. The session was conducted on July 21, 2025, for students in grades IV–VI using an interactive presentation method with a projector, accompanied by an evaluation quiz. The results showed high enthusiasm and improved understanding among students regarding the material presented. The education program proved effective in fostering awareness of maintaining bodily boundaries and reporting incidents of abuse. It is recommended that sex education be integrated sustainably into the curriculum, supported by gender sensitive teacher training, and active involvement of parents and the community to create a safe environment for children.